2017
DOI: 10.4149/neo_2017_407
|View full text |Cite
|
Sign up to set email alerts
|

FBP1 modulates cell metabolism of breast cancer cells by inhibiting the expression of HIF-1α

Abstract: This study aimed to investigate the function of fructose-1, 6-bisphosphatase 1 (FBP1) in regulating cell growth and metabolism through hypoxia-inducible factor 1α (HIF-1α)-dependent hypoxic response in breast cancer cells. Two human breast carcinoma cell lines, including luminal-like cell line MCF-7 and basal-like cell line MDA-MB-468, were cultured under hypoxia condition, then the expressions of FBP1 and HIF-1α were detected by western blotting. In addition, up-regulated FPB1 in MDA-MB-468 cells were induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 34 publications
(38 reference statements)
4
18
0
Order By: Relevance
“…FBP1 has been reported to inhibit HIF-1α activity or expression (27,46). The present study also revealed that knockdown of FBP1 increased the expression of HIF-1α in HCC cells.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…FBP1 has been reported to inhibit HIF-1α activity or expression (27,46). The present study also revealed that knockdown of FBP1 increased the expression of HIF-1α in HCC cells.…”
Section: Discussionsupporting
confidence: 76%
“…FBP1 can inhibit HIF-1α activity via direct interaction with the HIF-1α C-terminus. Furthermore, FBP1 was reported to modulate cell metabolism of breast cancer cells by inhibiting the expression of HIF-1α (46). It was also revealed that knockdown of FBP1 increased the expression of HIF-1α (Fig.…”
Section: Overexpression Of Loxl2 or Knockdown Of Fbp1 Increases The Ementioning
confidence: 87%
“…Since the experiments were performed using antibodies that were unable to distinguish between Fbp isozymes (because of the high similarity of Fbp isoforms it is essentially not possible to obtain antibodies that are able to distinguish between the two physiological, globular forms of Fbp isozymes) we tested whether the levels of Ldha and Hif1α in cancer cells depend on Fbp2 amount or the consequences of Fbp2-Hif1α interactions that are not related to glycolysis. It has been previously shown that, in cancer cells, the overexpression of Fbp1 and Fbp2, respectively, stimulated Hif1α degradation [31], suppressed glucose metabolism, and reduced cell proliferation [32]. Our results reveal that, in the KLN205 cells, the partial (about 50%) silencing ( Figure 6A) of Fbp2 expression with shRNA very significantly increased Hif1α and Ldha levels ( Figure 6B,C).…”
Section: Resultssupporting
confidence: 60%
“…Glycolytic antagonist, negative regulator of HIF1α and PKM2 (53). Epigenetic silencing promotes glycolysis, and decreased oxygen consumption and ROS production (37).…”
Section: Fbp1 Oxidative Phosphorylationmentioning
confidence: 99%
“…Master metabolic regulator and transcription factor that upregulates glucose transporters and glycolytic enzymes, including PDK1 and PKM2 (37,53,55,56). Also promoted the shift toward oxidative epithelial-like CSC state (46).…”
Section: Hif-1α Glycolysis Oxidative Phosphorylationmentioning
confidence: 99%